2014
DOI: 10.3171/2013.9.jns122133
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical resection of extensive craniopharyngiomas using a frontolateral approach: operative technique and outcome

Abstract: Object. An extensive craniopharyngioma is a tumor that extends into multiple compartments (subarachnoid spaces) and attains a size larger than 4 cm. A wide spectrum of approaches and strategies has been used for resection of such craniopharyngiomas. In this report the authors focused on the feasibility and efficacy of microsurgical resection of extensive craniopharyngiomas using a frontolateral approach.Methods. A retrospective analysis was performed on 16 patients with extensive craniopharyngiomas who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Table 6 lists the surgical approaches utilized in previous large series. 4,6,8,10,21,24,25 We created a lesion classification that could be used to determine the most appropriate surgical approach. Lesion identification and the approach used during the resections were as follows.…”
Section: Criteria For Selecting Surgical Approaches Based On An Anatomentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 lists the surgical approaches utilized in previous large series. 4,6,8,10,21,24,25 We created a lesion classification that could be used to determine the most appropriate surgical approach. Lesion identification and the approach used during the resections were as follows.…”
Section: Criteria For Selecting Surgical Approaches Based On An Anatomentioning
confidence: 99%
“…However, the optimal surgical approach remains controversial. 4,6,8,10,12,21,24,25 AbbreviAtioNs GTR = gross-total resection; KPS = Karnofsky Performance Scale; NTR = near-total resection; PR = partial resection; STR = subtotal resection; VIS = visual impairment score. objeCtive Craniopharyngiomas remain a particularly formidable challenge in the neurosurgical field.…”
mentioning
confidence: 99%
“…These generally include the pterional (frontotemporal), orbitozygomatic, and lateral supraorbital (frontolateral) approaches. 20,24,46,59 While all of these approaches typically use a curvilinear incision behind the hairline, the latter group of supraorbital approaches can also be performed with smaller eyebrow or eyelid incisions. 15,21,50,57 These are familiar approaches that provide a short route to the suprasellar region and are particularly useful for tumors that exhibit lateral extension into the sylvian fissure.…”
Section: Anterolateral Transcranial Approachesmentioning
confidence: 99%
“…15,21,50,57 These are familiar approaches that provide a short route to the suprasellar region and are particularly useful for tumors that exhibit lateral extension into the sylvian fissure. Recently, Gerganov et al 24 reported excellent outcomes with an 87% rate of gross-total resection of extensive craniopharyngiomas using a more simple frontolateral craniotomy. While there are a variety of anterolateral approaches, we prefer the one-piece modified orbitozygomatic approach.…”
Section: Anterolateral Transcranial Approachesmentioning
confidence: 99%
See 1 more Smart Citation